Antiferromagnetic self-ordering of a Fermi gas in a ring cavity. (15th April 2019) - Colella, Elvia; Ostermann, Stefan; Niedenzu, Wolfang; Mivehvar, Farokh; Ritsch, Helmut
Abstract: We explore the density and spin self-ordering of driven spin-1/2 collisionless fermionic atoms coupled to the electromagnetic fields of a ring resonator. The two spin states are two-photon Raman-coupled via a pair of degenerate counterpropagating cavity modes and two transverse pump fields. In this one-dimensional configuration the coupled atom-field system possesses a continuous U (1) translational symmetry and a discrete Z 2 spin inversion symmetry. At half filling for sufficiently strong pump strengths, the combined U (1) × Z 2 symmetry is spontaneously broken at the onset of a superradiant phase transition to a state with self-ordered density and spin structures. We predominately find an antiferromagnetic lattice order at the cavity wavelength. The self-ordered states exhibit unexpected positive momentum pair correlations between fermions with opposite spin. These strong cavity-mediated correlations vanish at higher pump strength.